Заходи щодо подолання наслідків фрагментації земель сільськогосподарського призначення: європейський досвід та українські реалії - Попов, Андрій Сергійович; Popov, Andriy (Kharkiv : KNAU, 2016)
UA: Проведення земельної реформи в Україні призвело до подрібнення земель сільськогосподарського призначення. У статті наводиться характеристика європейських заходів щодо зменшення рівня фрагментації земель сільськогосподарського призначення. Визначено, що в українських умовах застосування європейських заходів з подолання фрагментації земель у класичному (традиційному) розумінні неможливе. EN: One of the land reform implementation results in Ukraine is the distribution of the state-owned agricultural land to the rural population in the form of physical land parcels. As a consequence, however, the land was subdivided into many small units. This land fragmentation has led to fundamental changes in the formation of the new agricultural enterprises and brought some negative consequences in their functioning. The problem of the land fragmentation in Ukraine is quite new and uninvestigated. The aim of the article is to analyze the existing measures (instruments) in European countries for reducing the effects of agricultural land fragmentation and to determine the possibility of «transplantability» of Western experience to Ukraine. The principal measures to decrease the agricultural land fragmentation in European countries are: voluntary parcel exchange, land banking and land consolidation. The article presents the characteristics and comparative analysis of these measures. One of the four types of land fragmentation is a main problem of Ukraine, namely the discrepancy between the landownership and the land use. The Western European countries have been used the three instruments for reducing only two types of land fragmentation: the land use fragmentation and the internal fragmentation. Consequently, the using of Western European measures to decrease agricultural land fragmentation is impossible without their adaptation to the Ukrainian realities. Therefore, the actual problem in Ukraine today is to find the own measures to overcome the problem of agricultural land fragmentation based on the Western European experience.
Measures to overcome consequences of agricultural land fragmentation: european experience and ukrainian realities
Keywords: фрагментація земель; земельний банк; консолідація земель; земельна ділянка; обмін; заходи; land fragmentation; land banking; land consolidation; land parcel; exchange; measures